Integrating Sustainability, Occupational Health and Safety, and Organizational Culture: A New Framework for Enhancing Corporate Performance in Indonesian Port Management - Bondan Winarno; Moiko Sivatino; Eky Silizar Rahman; Aghissiva Antasya Rahma; Ela Noor Fithri Kumala (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This study examines the strategic integration of sustainability, occupational health and safety (OHS), and organizational culture in Indonesian port management to improve corporate performance and operational resilience. The research was conducted due to the increasing complexity of port activities, environmental challenges, workplace safety risks, and the need for adaptive organizational governance in supporting sustainable maritime development. The study aims to formulate a comprehensive and integrated framework that strengthens organizational effectiveness through the alignment of sustainability practices, OHS implementation, and organizational culture. This research employed a Systematic Journal Review (SJR) design by following the PRISMA guidelines to identify, screen, and evaluate relevant scientific publications from major international databases. Data were analyzed using thematic synthesis to ensure the credibility, consistency, and reliability of the findings. The results indicate that the integration of sustainability, OHS, and organizational culture contributes significantly to improving operational efficiency, employee productivity, environmental responsibility, and safety performance in port management systems. The findings further reveal that organizational culture functions as a strategic mediator that reinforces policy implementation, strengthens employee engagement, enhances communication effectiveness, and supports long-term organizational adaptation. Several reviewed studies also reported reductions in workplace accidents, improved environmental management, increased service quality, and stronger stakeholder trust. Therefore, the study concludes that an integrated management framework is essential for creating sustainable, safe, and high-performing port organizations in Indonesia.